2006
DOI: 10.1021/jf060344u
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enzymatic Deamidation by Protein-Glutaminase on Structure and Functional Properties of Wheat Gluten

Abstract: Protein-glutaminase (PG) purified from Chryseobacterium proteolyticum was used to investigate its deamidation effects on wheat gluten. Water-insoluble gluten was able to be deamidated to the extent of deamidation degree (DD) 72% in 200 mM sodium phosphate buffer (pH 7) at 40 degrees C for 30 h. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis exhibited an upper shift of gluten bands with only deamidation for 1.5-2.0 h (DD 35-45%) compared to the bands of nondeamidated gluten. Results of Fourier transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
118
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 38 publications
(59 reference statements)
15
118
0
1
Order By: Relevance
“…3). Second derivative of amide I region (1600-1700 cm À1 ) of the spectrum was investigated and the peaks at 1620 and 1630 cm-1 (b sheet), 1650 cm-1 (a helix), 1666 cm-1 (b turn structure) and 1680 cm-1 (intramolecular b sheet) (Yong, Yamaguchi, & Matsumura, 2006) were evident (Fig. 2).…”
Section: Bandmentioning
confidence: 99%
“…3). Second derivative of amide I region (1600-1700 cm À1 ) of the spectrum was investigated and the peaks at 1620 and 1630 cm-1 (b sheet), 1650 cm-1 (a helix), 1666 cm-1 (b turn structure) and 1680 cm-1 (intramolecular b sheet) (Yong, Yamaguchi, & Matsumura, 2006) were evident (Fig. 2).…”
Section: Bandmentioning
confidence: 99%
“…This enzyme was discovered in the culture supernatant of Chryseobacterium proteolyticum (Yamaguchi and Yokoe 2000;Yamaguchi et al 2001), and its action was investigated on several food proteins Gu et al 2001;De Jong and Koppelman 2002;Yong et al 2004Yong et al , 2006. On skim milk proteins, Miwa et al (2010) showed that deamidation increased the electronegativity of caseins due to the formation of supplementary carboxyl groups leading to a reduction of the pHi toward lower pH.…”
Section: Deamidationmentioning
confidence: 99%
“…Although the deamidation of proteins can be performed either enzymatically or nonenzymatically (i.e., chemically), enzymatic protein modification has several advantages over chemical treatment, such as milder reaction conditions, increased reaction rate, and higher specificity. Specifically, transglutaminase, protease, peptidoglutaminase, and protein-glutaminase enzymes have been shown to catalyze protein deamidation (5,6,26,34).Soy sauce is a traditional Japanese seasoning that is manufactured by fermenting steamed soybeans and roasted wheat with koji molds (Aspergillus sojae or Aspergillus oryzae) along with water and salt. A. sojae is preferentially used to make soy sauce due to its high proteolytic activity.…”
mentioning
confidence: 99%